Descripción de Sichuanolenus Zhang & Zhu en Chang et al. (1980) del sur de China y su importancia bioestratigráfica (2020)
In the Paleozoic Era and specifically in the Cambrian Period, trilobites have been useful to determine biostratigraphy and international correlation. The genus Sichuanolenus Zhang & Zhu in Chang et al. (1980) lived in this period, in the southeast of China, on the Yangtze platform. This genus is important because it helps the reconstruction of the Cambrian faunal succession in its area and for the correlation between eastern and western Gondwana. Also, this genus makes part of the Ellipsocephalidae Family (Matthew, 1892) which was quite numerous in the Lower Cambrian and it has been found in different environment and regions of the world. Sichuanolenus Zhang & Zhu in Chang et al. (1980) was described in the 1980s, being the only description and since then there has not been a formal description neither reconstruction. Additionally, the genus Protolenus Matthew, (1892), lived in western Gondwana and it can be observed that it has morphological similarities with Sichuanolenus Zhang & Zhu in Chang et al. (1980). This work re-describes Sichuanolenus Zhang & Zhu in Chang et al. (1980) and makes a comparison of this with Protolenus Matthew, (1892), leaving a suggestion of a possible synonymy between these two genus and the international implications that this would bring between east and west Gondwana.